JUSTICE OF INHERITANCE RIGHTS FOR WOMEN IN SAHU TRIBE CUSTOMARY LAW: A COMPARATIVE STUDY AND EFFORTS TOWARD HARMONIZATION - Nam Rumkel; Muhamad Taufik La Ode (Cepalo, 2025)
Indonesia's legal pluralism allows customary and national laws to coexist, presenting challenges in inheritance and gender justice. The Sahu Tribe's inheritance system in West Halmahera follows patriarchal, patrilineal principles, where inheritance is restricted to male heirs, leaving women without rights, even in the case of only daughters. This creates gender inequality and contradicts civil law, which guarantees equal inheritance rights. This normative legal research, using a comparative approach, analyzes the alignment of the Sahu Tribe's inheritance system with justice principles and compares it with civil law’s inclusive protection of women’s rights. The study proposes harmonizing customary and national law to create a fairer inheritance system. Findings suggest that civil law intervention, through reinterpretation of customary values, human rights alignment, and shifts in community attitudes, is necessary to reduce gender injustice. A more inclusive, bilateral inheritance codification is needed to preserve customary diversity while ensuring justice, with gender-responsive laws promoting equality and encouraging indigenous communities toward a more egalitarian system.